SISTEM PRODUK INOVASI DEBOPAY DALAM MENGOPTIMALISASIKAN DANA DESA DI DESA KLAMBIR LIMA KEBUN - Franita, Riska; Lubis, Hidayati Purnama; Yazid, Ahmad (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2022)
This research is an innovation product made by the research team for Kelambir Lima Village. This research is an applied research using secondary and primary data and the results of the research that this debopay product can become an icon of kelambir lima village products. This research is very useful because it creates product innovations, cost reports, and making strategies for innovation products debopay. With the results of this research, it is hoped that it can form an independent community in creating opportunities to develop UMKM in the digital era